Depression in brain tumor patients: early detection and screening - Finze, Alida; Deleanu, Laura; Weiß, Christel; Ratliff, Miriam; Seiz-Rosenhagen, Marcel (Supportive care in cancer, 2023)
Depression is reported in up to 90% of cancer patients but to this date, a standardized screening tool for depression specifically modified for patients diagnosed with brain tumors is lacking. Thus, this study aims to develop an adapted screening tool and identify a suitable time slot for screening.